Verificação de identidade profissional utilizando análise exploratória de dados e a análise estruturada de redes: o caso do CI-Brasil e da microeletrônica no CNPq - Sarmento, Alexandre Guilherme Motta (2016)
We propose a preliminary model for perception analyses of professional identity based on quantitative criteria as applied to a specific academic area. The identity is a largely discussed by social sciences and there is a consensus about the difficulties in describing its social construction and even its perception by the subjects themselves. Professional identity is not different. Here, we studied how public policies aimed at academic and professional consolidation and training for the microelectronics sector may have had influence on its trainees and professionals over the last decade. We used social network analysis tools on Lattes curricula to determine semantic similarities between bibliographic productions of researchers who applied projects to the CNPq CA-ME and of trainees under CI-Brazil Program. We then used the colected data to characterize, from the distribution of keywords colleted throughou time, the identity evolution of the subjects. This paper concerns itself also with a brief presentation and evaluation of the CI-Brasil program as such (i.e., a program). Initiated in 2002, it has helped the alteration of the microelectronic ecosystem in the country, especially regarding training and fixation of human resources for the integrated circuit design sector. Embedded electronics have been partially responsible for deficits in the Brazilian trade balance. Therefore, public policy must be formulated cautiously and responsibly so as to increase sector infrastructure and form adequate human resources regarding market demand, be it at technician, undergraduate or graduate levels, and training these professionals. This paper focuses on undergraduate degrees and other training initiatives. Finally, this paper aims to indicate indispensable requirements for the assimilation of these professionals by the market, with public support and financing in partnership with universities and private enterprises (triple helix.)